Postnatal Antioxidant and Anti-inflammatory Treatments Prevent Early Ketamine-Induced Cortical Dysfunctions in Adult Mice - Bove, Maria; Tucci, Paolo; Dimonte, Stefania; Trabace, Luigia; Schiavone, Stefania; Morgese, Maria Grazia (Frontiers in Neuroscience, 2020)
Early brain insult, interfering with its maturation, may result in psychotic-like disturbances in adult life. Redox dysfunctions and neuroinflammation contribute to long-term psychiatric consequences due to neurodevelopmental abnormalities. Here, we investigated the effects of early pharmacological modulation of the redox and inflammatory states, through celastrol and indomethacin administration, on reactive oxygen species (ROS) amount, levels of malondialdehyde (MDA) and antioxidant enzymes (superoxide dismutase 1, SOD1, glutathione, GSH and catalase, CAT), as well as of pro-inflammatory cytokines (tumor necrosis factor-alpha, TNF-α, interleukin-6, IL-6 and interleukin-1 beta, IL-1β), in the prefrontal cortex of adult mice exposed to a neurotoxic insult, i.e. ketamine administration, in postnatal life. Early celastrol or indomethacin prevented ketamine-induced elevations in cortical ROS production. MDA levels in ketamine-treated mice, also administered with celastrol, were comparable with the control ones. Indomethacin also prevented the increase in lipid peroxidation following early ketamine administration. Whereas no significant differences were detected in SOD1, GSH and CAT levels between ketamine and saline-administered mice, celastrol elevated the cortical amount of these antioxidant enzymes and the same effect was induced by indomethacin per se. Both celastrol and indomethacin prevented ketamine-induced enhancement in TNF-α and IL-1β levels, however they had no effects on increased IL-6 amount resulting from ketamine exposure in postnatal life. In conclusion, our data suggest that an early increase in cortical ROS scavenging and reduction of lipid peroxidation, via the enhancement of antioxidant defense, together with inhibition of neuroinflammation, may represent a therapeutic opportunity against psychotic-like disturbances resulting, later in life, from the effects of a neurotoxic insult on the developing brain.